2001
DOI: 10.1021/ma001417s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Structural and Topological Constraints on the Crystallization and Melting Behavior of Polymers:  3. Bisphenol A Polycarbonate

Abstract: In this paper, we report differential scanning calorimetry studies of the temperature and molar mass dependences for the primary and secondary crystallization behavior of bisphenol A polycarbonate (BAPC). The molar mass dependence of the crystallization rate is found to be much stronger during primary than during secondary crystallization, confirming our earlier claims that primary and secondary processes occur by significantly different mechanisms. Investigations of the secondary crystallization process sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
108
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(124 citation statements)
references
References 28 publications
16
108
0
Order By: Relevance
“…The crystallization temperature of PC may be independent of the molar mass however the crystallization kinetic depends strongly on the length of the chains and hence their mobility. [70] The crystallization is favorably observed for PC chains mixed with low molecular weight polymers. [71] In this study, SEC analyses prove that there are cleavages of the homopolymer PC chains, which increase the kinetic of crystallization.…”
Section: Dsc Analysismentioning
confidence: 99%
“…The crystallization temperature of PC may be independent of the molar mass however the crystallization kinetic depends strongly on the length of the chains and hence their mobility. [70] The crystallization is favorably observed for PC chains mixed with low molecular weight polymers. [71] In this study, SEC analyses prove that there are cleavages of the homopolymer PC chains, which increase the kinetic of crystallization.…”
Section: Dsc Analysismentioning
confidence: 99%
“…The saturated value of the heat of fusion (26 J/g) was in good agreement with what was reported before. 6 It was confirmed in Figure 5 that the concentration could be reduced to 0.1 wt % with keeping the crystallization effect from VGCF Ò and diminishing that from the matrix.…”
Section: Effect Of Carbon Materials On Induced Crystallizationmentioning
confidence: 74%
“…annealing at 185 C. 6 WAXD suggested a distinguished peak appeared at 17.3 deg (the mixture of (020) (17.0 deg) and (202) (17.6 deg) diffraction of PC) when annealing around 200 C only for 2 h. 16 DSC and WAXD results allowed us to say that PC crystallization was enhanced in the presence of VGCF Ò . Dynamic melt rheological property as a function of time suggested the increase of storage and loss moduli around 200 C. It was reported that MWCNT also crystallizes a certain type of thermoplastic polyimide and polypropyrene.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…PC could not crystallize under these conditions even though PC crystallization has been previously reported. [32,33] At 180 8C, PC is in a highly elastic state. where the relaxation time of physical entanglements between chains is considerably higher compared to the solidification time.…”
Section: Morphology Of Pc/hdpe Microfibrillar Blendsmentioning
confidence: 99%